Adaptive Stress Response Pathways Induced by Environmental Mixtures of Bioaccumulative Chemicals in Dugongs - Jin, Ling; Gaus, Caroline; Escher, Beate I. (Environmental science & technology, 2015)
To address the poorly understood mixture effects of chemicals in the marine mammal dugong, we coupled equilibrium-based passive sampling in blubber to a range of in vitro bioassays for screening mixtures of bioaccumulative chemicals. The modes of action included early effect indicators along important toxicity pathways, such as induction of xenobiotic metabolism, and some integrative indicators downstream of the molecular initiating event, such as adaptive stress responses. Activation of aryl hydrocarbon receptor (AhR) and Nrf2-mediated oxidative stress response were found to be the most prominent effects, while the p53-mediated DNA damage response and NF-κB-mediated response to inflammation were not significantly affected. Although polychlorinated dibenzo-p-dioxins (PCDDs) quantified in the samples accounted for the majority of AhR-mediated activity, PCDDs explained less than 5% of the total oxidative stress response, despite their known ability to activate this pathway. Altered oxidative stress response was observed with both individual chemicals and blubber extracts subject to metabolic activation by rat liver S9 fraction. Metabolic activation resulted in both enhanced and reduced toxicity, suggesting the relevance and utility of incorporating metabolic enzymes into in vitro bioassays. Our approach provides a first insight into the burden of toxicologically relevant bioaccumulative chemical mixtures in dugongs and can be applied to lipid tissue of other wildlife species.